Use of botulinum toxin in the treatment of bruxism: A comprehensive analysis of diagnosis, treatment and their clinical correlations (Research, Society and Development, 2023)
The search for the use of botulinum toxin has increased exponentially in recent years due to its versatility in various aesthetic and therapeutic treatments. In Dentistry, the search for less invasive and more comfortable treatments has generated innovation in relation to the creation of new protocols and techniques, aiming for aesthetic and functional gains for patients. Among the various reasons for this search for the use of botulinum toxin is bruxism, which is characterized by teeth grinding or excessive compression, involving masticatory muscles such as the temporalis and masseter. This parafunctional habit can occur during sleep or while awake and causes a lot of damage to the stomatognathic system as a whole. The central objective of this work is to address the effectiveness of botulinum toxin in the treatment of bruxism. To this end, a literature review was carried out through scientific articles that addressed the toxin as a treatment option for this parafunction. The platforms were used: Pub Med, Google Scholar and Scielo, using the descriptors: botulinum toxin, bruxism, therapeutic and their effectiveness and possible adverse effects were discussed.